Why are so few females promoted into CEO and vice-president positions? Danish empirical evidence 1997-2007 - Nina Smith; Valdemar Smith; Mette Verner (Institute for the Study of Labor (IZA), 2011)
In most OECD countries, only very few women succeed in reaching top executive positions. In this paper, the probability of promotion into VP and CEO positions is estimated based on employer-employee data on all Danish companies observed during the period 1997-2007. After controlling for a large number of family-related variables, including take-up history of maternity and paternity leave and proxies for female-friendly companies, there is still a considerable gap in the promotion probabilities for CEO positions, but not for VP positions. Thus, the results cannot confirm recent theories on belief flipping or disappearance of statistical discrimination against women who succeed getting into career track positions. The results reflect that the hiring decision and the decision to enter a top position as 'number one', i.e. CEO, in the organization is very different from the decision to hire or become VP, i.e. number two or lower.
urn:nbn:de:101:1-201110053356
Keywords: G34; J16; J24; M51; 330; promotion; top executive positions; statistical discrimination; Weibliche Arbeitskräfte; Erwerbsverlauf; Geschlechterdiskriminierung; Dänemark